Variation in Genetic Mechanisms for Plumage Polymorphism in Skuas (Stercorarius) - Janssen, Kirstin; Bustnes, Jan Ove; Mundy, Nicholas I (Journal of Heredity, 2021)
Coloration is evolutionarily labile and so provides an excellent trait for examining the repeatability of evolution. Here, we investigate the repeatability of the evolution of polymorphic variation in ventral plumage coloration in skuas (Stercorarius: Stercorariidae). In 2 species, arctic (S. parasiticus) and pomarine skuas (S. pomarinus), plumage polymorphism was previously shown to be associated with coding changes at the melanocortin-1 receptor (MC1R) locus. Here, we show that polymorphism in a third species, the south polar skua (S. maccormicki), is not associated with coding variation at MC1R or with variation at a Z-linked second candidate locus, tyrosinase-related protein 1 (TYRP1). Hence, convergent evolution of plumage polymorphisms in skuas is only partly repeatable at the level of the genetic locus involved. Interestingly, the pattern of repeatability in skuas is aligned not with phylogeny but with the nature of the phenotypic variation. In particular, south polar skuas show a strong sex bias to coloration that is absent in the other species, and it may be that this has a unique genetic architecture. Genotype to phenotype MC1R, melanin, repeatability of evolution, skua, TYRP1